A NOVEL TECHNIQUE TO ENHANCE DISSOLUTION RATE OF CILNIDIPINE USING LIQUISOLID COMPACT & WET GRANULATION (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
The main objective of the work was to improve the dissolution rate of the drug, Cilnidipine (CLD) by using the liquisolid compact technique and wet granulation. Cilnidipine drug is poorly soluble in water and it’s highly soluble in higher pH. In this study drug is solubilize in tween 80 and sodium hydroxide and meglumine solution. And then drug solution binding on Pearlitol SD 200. PVP K30 used as a binder and crospovidone used as a disintegrant. Sodium hydroxide and meglumine used as a buffering agent for basic media preparation. The drug release rates of tablets which prepared by liquisolid compact have higher solubility and dissolution than conventional tablets.